1986
DOI: 10.23986/afsci.72235
|View full text |Cite
|
Sign up to set email alerts
|

Control of manganese deficiency in sugar beet by placement of a manganated compound fertilizer

Abstract: Abstract. In Finland, manganese deficiency in sugar beet has traditionally been controlled by spraying the foliage with manganese sulphate. According to field experiments, placement of an acid compound fertilizer seems to provide a new possibility of controlling manganese deficiency of sugar beet in heavily limed fields. In 1-year experiments carried out in 1984-1985 in seven fields which showed slight symptoms of manganese deficiency, conversion from top dressing to the placement technique alone increased the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…An even better and more specific picture of the effect of fertilizer placement is obtained when the results of all experiments conducted at the Sugar Beet Research Centre are considered (e.g. Erjala 1986, Raininko 1988), comparing placement with broadcasting (Table 10). When evaluating the figures, one should take into consideration the fact that the number of trials and experimental fields varied from one year to another.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An even better and more specific picture of the effect of fertilizer placement is obtained when the results of all experiments conducted at the Sugar Beet Research Centre are considered (e.g. Erjala 1986, Raininko 1988), comparing placement with broadcasting (Table 10). When evaluating the figures, one should take into consideration the fact that the number of trials and experimental fields varied from one year to another.…”
Section: Discussionmentioning
confidence: 99%
“…The sugar beet was sown to stand, at a seed distance of 15 cm and row distance of 48 cm. The variety used was mostly Salohill in 1985 and1986; in some trials the cultivar Ovatio was also used.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Manganese helps in the production of enzymes used for metabolism of proteins and fat. Application of manganese @ 25-30 kg ha -1 together with compound fertilizer increased the average root yield by 2.0 t ha -1 (+7%) compared to manganese-free compound fertilizer (Erjala, 1986). Mekki (2014) reported that Manganese as sole treatment increased root length and diameter as well as fresh root weight of sugar beet.…”
Section: Manganese and Other Micro Nutrientsmentioning
confidence: 99%